Laser Auto Level In Lathe Life Center untuk Meningkatkan Kinerja Mesin Bubut di Laboratorium Teknik Pemesinan - Yogasmana, Yopi; Barmana, Doni (Jurnal Pengelolaan Laboratorium Pendidikan, 2024)
The performance of a lathe in the turning process is greatly influenced by the components in the lathe itself such as the fixed head, removable head, rotating center, lathe tool, drill chuck and center drill. Reduced lathe performance can cause lathe failure. The incision made by the lathe chisel on the workpiece will determine the result of the turning work. The cylindricity/flatness of the workpiece results from the parallelism of the lathe tool and the workpiece axis. If the lathe tool is not parallel to the workpiece axis, it will produce a workpiece that is oval (not cylindrical) or has an uneven surface. In aligning the lathe tool on the workpiece axis, you must first bring the lathe tool closer to the end of the rotating center, which sometimes takes quite a long time. Laser Auto Level in Lathe Life Center (LAL3C) is a hand tool that functions to make it easier to align the lathe tool on the workpiece axis as an effort to improve the performance of the lathe machine. The research results show that using LAL3C can make it easier to align the lathe tool on the workpiece axis and can shorten the time.